Fears of Violence During Morning Travel to School - Allison, Paul D (Journal of adolescent health, 2013)
PURPOSE: Children's safety as they travel to school is a concern nationwide. We investigated how safe children felt from the risk of being assaulted during morning travel to school. METHODS: Children between 10 and 18 years old were recruited in Philadelphia and interviewed with the aid of geographic information system (GIS) mapping software about a recent trip to school, situational characteristics, and how safe they felt as they travelled based on a 10-point item (1 = very unsafe, 10 = very safe). Ordinal regression was used to estimate the probability of perceiving different levels of safety based on transportation mode, companion type, and neighborhood characteristics. RESULTS: Among 65 randomly selected subjects, routes to school ranged from 7 to 177 minutes (median = 36) and .1-15.1 street miles (median = 1.9), and included between 1-5 transportation modes (median = 2). Among students interviewed, 58.5% felt less than very safe (i.e.,8, for example, was .99 while in a car and .94 while on foot but was .86 and .87 when on a public bus or trolley. Probability was .98 while with an adult but was .72 while with another child and .71 when alone. Also, perceived safety was lower in areas of high crime and high density of off-premise alcohol outlets. CONCLUSIONS: Efforts that target situational risk factors are warranted to help children feel safe over their entire travel routes to school